2010
DOI: 10.1063/1.3455892
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the anion on the electrical conductivity and glass formation of 1-butyl-3-methylimidazolium ionic liquids

Abstract: Six ionic liquids based on the 1-butyl-3-methylimidazolium cation have been studied. As anions Cl(-), Br(-), I(-), [NCS](-), [N(CN)(2)](-), and [BF(4)](-) were selected. The electrical conductivities were determined between 173 and 393 K based on impedance measurements in the frequency range from 0.1 to 10(7) Hz. The electrical conductivity increases, whereas the glass transition temperature, the fragility, and the low temperature activation energy decrease with increasing anion size. The results can be unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
51
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 48 publications
7
51
0
Order By: Relevance
“…Both, the main relaxation time and the dc conductivity reveal the typical non-Arrhenius temperature dependence known from glass forming systems. Such behavior was reported for many ionic liquids 25,32,34,50,53,55,56,57,58,59,60,61 . Fits (solid lines) with the empirical Vogel-Fulcher-Tammann (VFT) law 62,63,64,65 ,…”
Section: Dielectric Spectroscopysupporting
confidence: 69%
“…Both, the main relaxation time and the dc conductivity reveal the typical non-Arrhenius temperature dependence known from glass forming systems. Such behavior was reported for many ionic liquids 25,32,34,50,53,55,56,57,58,59,60,61 . Fits (solid lines) with the empirical Vogel-Fulcher-Tammann (VFT) law 62,63,64,65 ,…”
Section: Dielectric Spectroscopysupporting
confidence: 69%
“…25 Xu et al 26 studied qualitative fragilities of aprotic ionic liquids using the T gscaled Arrhenius plot of viscosity, and the fragility of the ILs was found to range from intermediate to very fragile, depending on the ionic structure. In a quantitative study of m-fragility for a series of n-alkylimidazolium tetrafluoroborate with different alkyl chain length, Leys and co-workers 27 reported that alkyl chain length had a little effect.…”
Section: Introductionmentioning
confidence: 98%
“…4 Broadband impedance spectroscopy has been extensively used to characterize ion transport and dielectric relaxation processes in ionic liquids. [5][6][7][8][9] In this method, low ac electric fields are applied, and the linear current response is measured. However, when the ac electric fields applied to ionic conductors (solid and liquid) are increased to values beyond 50-100 kV/cm, the current response becomes nonlinear.…”
Section: Introductionmentioning
confidence: 99%